(untitled) (Teología, 2016)
The question that guides this work is referred to the possibility of extracting some epistemological perspectives of the production of a memorial space. Its theme is related to the ways of developing the social trauma. Historical time to which it refers is the last civic-military dictatorship (March 1976- December 1983). The route of this contribution has three parts. In the first, we consider the notions of body and narration; the second presents outlines of answers to the question posed, and the third is briefly referred to two European and Christian women: Alice Domon (France, 1937- Argentina, 1977) and Elisabeth KÁ¤semann (Germany, 1947- Argentina, 1977). Both lived in Latin America and can be considered true humanitarian spaces of peace.